CLIMATE JUSTICE IN THE PERSPECTIVE OF MAQASID AL-SHARIAH: ITS IMPLICATIONS FOR ENVIRONMENTALLY-ORIENTED ISLAMIC EDUCATION TEACHING MATERIALS - Rasmuin (As-Sulthan Journal of Education, 2025)
The global climate crisis has evolved from a mere environmental issue into a profound crisis of justice, with its impacts felt disproportionately by developing countries and vulnerable groups. Indonesia, with its high geographical and socio-economic vulnerability, has become one of the main arenas for the manifestation of this climate injustice. This article, compiled through qualitative literature study methods, argues that Islamic Education has a strategic role in shaping climate justice awareness and ethics. Still, its potential has not been optimally exploited. The analysis shows a significant gap between the visionary curriculum objectives and the teaching materials, which tend to be partial and do not respond to the urgency of the crisis. This article proposes an ethical framework rooted in Maqasid al-Shariah to bridge this gap. By reconceptualising Maqasid and placing environmental preservation (Hifz al-Bi'ah) as the foundation for the other five essential pillars (al-dharuriyyat al-khamsah), this framework can transform the discourse from mere nature conservation to the struggle for justice. The implications of this framework demand a double transformation in Islamic Education: content enrichment that integrates contextual case studies of climate justice in Indonesia, a deepening of ecological interpretation, and a methodological revolution through the adoption of action-oriented Project-Based Learning (PjBL). This transformation is expected to equip the younger generation of Muslims to become agents of change who can respond to the challenges of climate justice in a critical and constructive